Effect of wind shield on heat transfer to pot of KB-5 cooking stove by computational fluid dynamics - Wichangarm, Mana; Kaewpho, Pattanapong (RMUTSB ACADEMIC JOURNAL, 2023)
The objective of this research was to study effect of wind shield on heat transfer to pot of KB-5 cooking stove by computational fluid dynamics and experiment. The simulation model was created by ANSYS 21. Heat transfer to pot of stove with wind shield being, model B (cylindrical wind shield), model C (inverted cone wind shield) and model D (upturned cone wind shield) were compared with KB-5 original stove model A (without wind shield). Analyze the thermal efficiency and heat transfer to pot on total heat flux was conducted. The results showed that model C is inverted cone wind shield allows the flame to flow together in the center of the combustion chamber before flowing to pot, thus causing model C had the highest thermal efficiency and total heat flux. model C had the highest thermal efficiency of 46.18%, followed by model B, model D and model A with thermal efficiency of 43.62, 41.52 and 39.15%, respectively, or model C increased in thermal efficiency by 5.54, 10.09 and 15.22% compared to model B, model D and model A, respectively. model C had the highest total heat flux of 24.73 kW/m2, followed by model B, model D and model A with thermal efficiency of 22.18, 20.96 and 18.32 kW/m2, respectively, or model C had total heat flux increase of 10.31, 15.24 and 25.93% compared to model B, model D and model A, respectively.